The Development and Effectiveness of Interactive Multimedia-Based Nutrition Education Module (IMNEM): A Concept Paper - Ismail, Susheela; Mohd Nor, Nurfarhana Diana; Abdullah, Nurul Fadhilah (Southeast Asia Early Childhood Journal, 2024)
Globally, malnutrition is an issue that has never been overcome, even after a series of efforts by experts, which have never been impressive. The world’s malnutrition burden remains unsatisfactory since malnutrition is solely responsible for more illnesses than other reasons. Malnutrition continues to be a significant problem in Malaysia. The most common manifestation of chronic malnutrition in children is stunting, a lifetime problem for a child in Malaysia. Stunting is an irreversible condition in which a child cannot regain their height in the same way that they can regain weight. Notably, various factors have been identified associated with the risk of stunting among Malaysian children. This includes socio-demographic background, gestational characteristics, maternal and infant diet, feeding practice, illness, and infection. As discovered through the literature review, stunted children face many disabilities, such as learning deficiencies, which affect their productivity for economic prosperity, mostly falling sick more often, losing opportunities to learn, performing poorly in school and growing up to be backward, and more likely to suffer from diet-related Non-Communicable Diseases (NCDs). Therefore, this study will develop and evaluate the effectiveness of interactive multimedia-based nutrition education on Knowledge, Attitude, and Practice (KAP) about nutrition, growth monitoring, breastfeeding, and child-feeding practices among mothers with stunted children using the ADDIE model. This study will employ a quasi-experimental research method consisting of control and treatment groups. The study will be conducted in maternal child health clinics in the Seberang Perai district in Pulau Pinang. The population of this study consists of mothers with stunted children under five years old. In this study, convenience sampling will be used to recruit the target population, and the sample size was determined using G*power.